A Multi-Objective Model for Sustainable Reverse Logistics Design for End-Of-Life Tires Under a Regulatory Framework: A Chilean Case Study - Espinoza-Perez, A (Institute of Electrical and Electronics Engineers Inc., 2023)
Growing concern about environmental pollution has led to a tightening of legislation worldwide. An example is the Extended Producer Responsibility (EPR) principle, which holds producers responsible for the life-cycle management of their products. In this context, the management of End-of-life tires (ELT) presents a significant challenge due to the pollution they cause by being disposed of in landfills without prior treatment. Thus, there is an opportunity to implement ELT recovery technologies that explore new sustainable alternatives. This work presents a multi-period, multi-product, multi-objective optimization model that supports decision-making for the design of a sustainable reverse logistics network. A case study is presented to show the usefulness of this model, considering the implementation of pyrolysis plants for the treatment of ELT in Chile under the regulatory framework of the EPR Law. The results show that even though the objectives are opposed, the regulatory framework of the EPR Law allows for mitigating the conflict between economic, environmental, and social decisions by establishing collection goals. The epsilon-constraint method can find economically profitable solutions, obtaining gaps of at least 8.5% and at most 19.3%. However, this will depend on the changes and sensitivity of the uncertain parameters of the model. Conclusions call for reinforcement of regulatory policies involving reverse logistics and ELT management. Future work considers the implementation of robust optimization to deal better with uncertainty. © 2023 IEEE.